Pharmacokinetic Assessment of Drug‐Drug Interactions of Isavuconazole With the Immunosuppressants Cyclosporine, Mycophenolic Acid, Prednisolone, Sirolimus, and Tacrolimus in Healthy Adults. Issue 1 (25th July 2016) - Groll, Andreas H.; Desai, Amit; Han, David; Howieson, Corrie; Kato, Kota; Akhtar, Shahzad; Kowalski, Donna; Lademacher, Christopher; Lewis, William; Pearlman, Helene; Mandarino, Debra; Yamazaki, Takao; et al.
Abstract: This report summarizes phase 1 studies that evaluated pharmacokinetic interactions between the novel triazole antifungal agent isavuconazole and the immunosuppressants cyclosporine, mycophenolic acid, prednisolone, sirolimus, and tacrolimus in healthy adults. Healthy subjects received single oral doses of cyclosporine (300 mg; n = 24), mycophenolate mofetil (1000 mg; n = 24), prednisone (20 mg; n = 21), sirolimus (2 mg; n = 22), and tacrolimus (5 mg; n = 24) in the presence and absence of clinical doses of oral isavuconazole (200 mg 3 times daily for 2 days; 200 mg once daily thereafter). Coadministration with isavuconazole increased the area under the concentration‐time curves (AUC0–∞ ) of tacrolimus, sirolimus, and cyclosporine by 125%, 84%, and 29%, respectively, and the AUCs of mycophenolic acid and prednisolone by 35% and 8%, respectively. Maximum concentrations (Cmax ) of tacrolimus, sirolimus, and cyclosporine were 42%, 65%, and 6% higher, respectively; Cmax of mycophenolic acid and prednisolone were 11% and 4% lower, respectively. Isavuconazole pharmacokinetics were mostly unaffected by the immunosuppressants. Two subjects experienced elevated creatinine levels in the cyclosporine study; most adverse events were not considered to be of clinical concern. These results indicate that isavuconazole is an inhibitor of cyclosporine, mycophenolic acid, sirolimus, and tacrolimus metabolism.